Flourishing or Languishing? Description of Adolescents Mental Health in A Positive Continuum - Witdiawati Witdiawati; Syifa Imaniar Rahma; Dadang Purnama (GLOBAL HEALTH SCIENCE GROUP, 2025)
Mental health in adolescents is an important aspect in supporting optimal individual development during the challenges of transition. This study aims to identify the positive continuum of adolescent mental health. This is a quantitative descriptive study with a cross-sectional design. The study sample consisted of 250 adolescents (aged 14–18 years) at SMKN 2 Garut, selected using stratified random sampling. The research instrument used was the Mental Health Continuum-Short Form (MHC-SF). The results of this study indicate that 103 adolescents (41.2%) have moderate mental health categories. In the emotional well-being and social well-being dimensions, the majority of adolescents have low categories. Contributing factors include age, grade level, out-of-school activities, and places to confide. These findings emphasize the importance of promotional programs and optimizing the role of families to enhance adolescent well-being.